Impact of leadership self-efficacy and change- oriented behaviour on staff organizational citizenship behaviour in Nigerian Higher Education Institutions / Adebayo Saheed Adewale - Adebayo Saheed , Adewale (2018)
Education is the cornerstone of national development. Higher education institutions are responsible for producing skilled manpower needed to attain holistic and sustainable development. In order to make higher education institutions responsive and productive, effective leadership is needed. The self-efficacy and change-oriented behavior of academic leaders play a vital role in attaining organizational goals and development. This study examined the impact of leadership self-efficacy and change oriented behavior on staffs’ organizational citizenship behavior in public higher education institutions in Lagos State, Nigeria. It adopted an explanatory mixed method research design. A total of 420 staff were randomly selected from 10 public higher institutions in Lagos State for quantitative strand of this study, while 10 academic leaders participated in the qualitative strand of this study. The research instrument used in the quantitative strand was an adopted survey questionnaire. The questionnaire which consist of 62 items was used to gather information from staff for the quantitative strand while a semi-structured interview protocol consisting of 12 questions was used to collect information from the academic leaders for the qualitative strand in this study. The findings revealed that there is a positive and strong relationship between high self-efficacy and staff organizational citizenship behavior with r = .593 and p =.000. In addition, there exists a negative relationship between low self-efficacy and staffs’ organizational citizenship behavior with r = -.291 and p = .000 Furthermore, this study shows that there is a significant relationship between leadership self-efficacy and organizational citizenship behavior with estimate value of .172 and p-value of .000. Also, change-oriented behavior of leaders is significant to staff organizational citizenship behavior with estimate value of .273 and p-value of .000. Similarly, change policy was found to be significant to staff organizational citizenship behaviour with estimate value of .272 and p-value of .000. In addition, demographic information such as type of staff, staffs’ cadre and faculty do not have any effect on staff organizational citizenship behavior. Experience, type of institution and age of staffs have effect on staff organizational citizenship behavior in higher education institutions in Lagos State. The study further revealed that academic leaders developed their self-efficacy through personal development, experience and interaction with their society. In addition, good moral value, motivation, effective communication and good governance are measures employed by academic leaders in implementing change in higher education institutions. Also, it was found that academic leaders in public higher education institutions in Lagos State faced economic, social, political, human and resources challenges in the course of implementing change in their respective institutions. In order to ameliorate these challenges, the study proposed use of right personnel, self-reformation and good leadership. Finally, the findings revealed that personal, organizational, social and economic elements are responsible for staffs ‘organizational citizenship behaviour in public higher education institutions in Lagos State. In order to make public higher education institutions responsive to needs of their stakeholders, good governance, effective leadership and adequate facilities must be provided.